The political future of social security in aging societies - Galasso, Vincenzo, 1967- (MIT Press, 2006)
Doubts about the ability of industrialized countries to continue to provide a sufficient level of retirement benefits to a growing number of retirees has fueled much recent debate and inspired a variety of recommendations for reform. Few major reforms, however, have actually been implemented. In The Political Future of Social Security in Aging Societies, Vincenzo Galasso argues that the success of any reform proposals depends on political factors rather than economic theory. He offers a comparative analysis of the future political sustainability of social security in six countries with rapidly aging populations--France, Germany, Italy, Spain, the United Kingdom, and the United States. Using a quantitative approach, he finds that an aging population has political as well as economic effects: an older electorate will put pressure on politicians and policy-makers to maintain or even increase benefits. Galasso evaluates how each country's different political constraints shape its social security system, considering such country-specific factors as the proportion of retirees in the population, the redistributive feature of each system, and the existing retirement policy in each country. He concludes that an aging population will lead to more pension spending; yet postponing retirement mitigates the impact of this, and may be the only politically viable alternative for social security reform.